2011
DOI: 10.5539/ijb.v3n3p73
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Soil-Vegetation Interrelationships in a South-Southern Secondary Forest of Nigeria

Abstract: Multivariate statistical techniques were employed to study soil-vegetation interrelationships in a secondary forest of South-Southern Nigeria. The grid system of vegetation sampling was used to randomly collect vegetation and soil data from fifteen quadrats of 10m x 10m. The result of principal components analysis identified seven basic sets of soil-vegetation variables that enhanced the interrelationships. Canonical correlation result indicated a positive association between organic matter and tree size, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…Interpretation and identification of the significant variables on PCA bi-plot were carried out by the criterion provided by Legendre and Legendre (1998) and Iwara et al (2011). In this study, the cumulative percentage in PCA analysis conducted for gaining the weighting factors suggested that during all temporal events, the first four axes together accounted more than 80% variability (Table 5) and this proved the usefulness of this tool in this study (Wei-Giang and Bilquees 2008).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Interpretation and identification of the significant variables on PCA bi-plot were carried out by the criterion provided by Legendre and Legendre (1998) and Iwara et al (2011). In this study, the cumulative percentage in PCA analysis conducted for gaining the weighting factors suggested that during all temporal events, the first four axes together accounted more than 80% variability (Table 5) and this proved the usefulness of this tool in this study (Wei-Giang and Bilquees 2008).…”
Section: Resultssupporting
confidence: 57%
“…Similarly, the first four axes of PCA analysis carried out to characterize the temporal variations of land assessment parameters (RCS, revised SQI, HCS, and EMV) suggested 100% cumulative variability (Table 6), and usefulness of this tool was further proved by lack of any arch effect in PCA bi-plots (Figs 1 and 2). On each component, variable with loading ≥ 0.70 was identified as the significant variable (Iwara et al 2011;Mathur 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Squared cosines were used to link the variable with the corresponding axis and the greater the squared cosine, the greater the link with the corresponding axis. However, in order to determine basic soil, diversity (vegetation) and plant metabolites variables sustaining these interrelationships, the concept of component defining variables (CDV) which stipulates the selection and subsequent naming of variables with the highest component loading (correlation coefficient) as variables that provide the best relationships (Iwara et al, 2011;Mathur, 2012) was employed.…”
Section: Principal Component Analysis and Synthesis Of Datamentioning
confidence: 99%
“…(Hotelling, 1936) entre grupos de variables métricas, es decir, se analizaron las asociaciones entres conjuntos de variables. Este enfoque es ampliamente utilizado en el campo de las ciencias del suelo (Tan et al, 2003;Martin et al, 2005;Qi et al, 2009;Iwara et al, 2011;Silva Terra et al, 2014).…”
Section: Medidas Complementariasunclassified